2013
DOI: 10.15835/nsb549112
|View full text |Cite
|
Sign up to set email alerts
|

Classification of the Leguminosae-<i>Papilionoideae</i>: A Numerical Re-assessment

Abstract: The subdivision of the Leguminosae-Papilionoideae into taxa of lower rank was subject for major discrepancies between traditional classifications while more recent phylogenetic studies provided no decisive answer to this problem. As a contribution towards resolving this situation, 81 morphological characters were recorded comparatively for 226 species and infra-specific taxa belonging to 75 genera representing 21 of the 32 tribes currently recognized in this subfamily. The data matrix was subjected to cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In the present study, the applications of multivariate morphometric techniques resulted in the delimitation of 19 well-separated species of Lotus, and are clearly distinguished from each other. As a result of the cluster, PCoA, and PCA analyses six clear clusters are obtained and they correspond quite well with the species of Lotus accepted in Flora of Egypt (El Hadidy, 2003;Boulos, 2009;El-Gazzar et al, 2013). UPGMA gives insight into the degree of similarity among the OUT's and whether they form groups/clusters.…”
Section: Table (7)supporting
confidence: 59%
See 1 more Smart Citation
“…In the present study, the applications of multivariate morphometric techniques resulted in the delimitation of 19 well-separated species of Lotus, and are clearly distinguished from each other. As a result of the cluster, PCoA, and PCA analyses six clear clusters are obtained and they correspond quite well with the species of Lotus accepted in Flora of Egypt (El Hadidy, 2003;Boulos, 2009;El-Gazzar et al, 2013). UPGMA gives insight into the degree of similarity among the OUT's and whether they form groups/clusters.…”
Section: Table (7)supporting
confidence: 59%
“…In Egypt, the taxonomy of the genus Lotus has always been problematic which has been reflected in the number of its species (Täckholm, 1974;Boulos, 2009). Several studies have demonstrated the use of micromorphological characters to differentiate between some taxa of Fabaceae (Stenglein et al, 2003;Zorić et al, 2009;Saheed and Illoh, 2010;Albert and Sharma, 2013;El-Gazzar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…36 To narrow the range, PA1b-like peptides in the Fabaceae family were separated into tribes, on the basis of a limited range of floral characteristics, with a greater emphasis on petal morphology and stamen arrangement. 40 The aM1 diverged from leginsulin, PA1b and its isoforms from P. sativum, suggesting that there might be a close evolutionary relationship between aM1, PA1b, and leginsulin. Furthermore, in the Fabaceae family, most of the PA1b-like peptides belong to either the tribe of pea (Fabeae) or the tribe of soybean (Phaseoleae).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is hypothesized that the occurrence of chimeric structures of cliotides in the Fabaceae is the result of horizontal gene transfer between plant nuclear genomes or convergent evolution from PA1b-like peptides to cyclotides . To narrow the range, PA1b-like peptides in the Fabaceae family were separated into tribes, on the basis of a limited range of floral characteristics, with a greater emphasis on petal morphology and stamen arrangement . The aM1 diverged from leginsulin, PA1b and its isoforms from P. sativum , suggesting that there might be a close evolutionary relationship between aM1, PA1b, and leginsulin.…”
Section: Resultsmentioning
confidence: 99%
“…Phenetic studies of exomorphological characters can generate some accurate estimations of relationships between taxa (El-Hadidy et al, 2018). In a recent phenetic study on family Leguminosae, subfamily Papilionoideae in Egypt, all Egyptian species of Ononis were grouped together in one phenon along with some species of each Medicago, Trifolium and Lathyrus (El-Gazzar et al, 2013).…”
mentioning
confidence: 99%